The impact of the determinants of the supply and demand sides on the financial depth of a sample of Arab countries (2014-2021) - Ilifi Mohamed; Belghalem Hamza (Journal of North African Economies, 2025)
In this study, we aim to try to answer the research problem of showing the effect of the variables of supply and demand on the financial depth of a sample of Arab countries for the period 2014-2021, within two main axes, The first deals with the concept of financial depth, while the second seeks to build a standard model using plate models, Based on this, we Based on that, we concluded that openness in its financial and commercial form, the development of financial intermediation activity, and the existence of appropriate economic policies with the availability of regulatory and legislative frameworks (institutional development) positively affect the financial depth.